Case Report: Clinical presentations of cyanosis associated with acquired methemoglobinemia in infants—a clinical challenge - Wang, Lin; Ye, Yang; Li, Delian; Li, Kexing; Yang, Peng; Hu, Huanrui; Liu, Xiaoliang; Zhao, Yongmei (Frontiers in Pediatrics, 2025)
BackgroundCyanosis is a common clinical finding in infants and children. Particularly, central cyanosis can be associated with significant and potentially life-threatening diseases. Acquired methemoglobinemia is a rare but severe or even fatal cause of cyanosis in infants. Due to its rarity, timely diagnosis and appropriate management, particularly in infants, can be challenging in a clinical setting.Case reportWe report the case of a previously healthy 49-day-old female infant who presented with central cyanosis. Four hours prior to presentation, her guardian had inappropriately prepared her milk formula using spinach juice. This critical clue hinted to us that this infant might suffer from acquired methemoglobinemia. Upon blood sampling, her blood appeared chocolate brown in color. Furthermore, arterial blood gas analysis revealed abnormal findings, with a significantly elevated percentage of methemoglobinemia at 44.7%. Regarding the history of inappropriate formula preparation using vegetable juice and the abnormal finding of methemoglobinemia, a diagnosis of acquired methemoglobinemia was proposed. Other causes of methemoglobinemia were further excluded. Treatment with methylene blue and vitamin C was immediately initiated. Encouragingly, the cyanosis of this infant resolved 1 h later, with normal results of the repeated blood gas analysis. This infant was discharged home 2 days later and had no abnormal findings during the follow-up.ConclusionIn this study, we reported a rare case of acquired methemoglobinemia in a 49-day-old infant. Inappropriate preparation of the infant milk formula with spinach juice was the potential cause of methemoglobinemia in this case, which presented with central cyanosis. Our findings also suggested that pediatricians should be aware of acquired methemoglobinemia as a potential cause of cyanosis in infants.